Power loss analysis on the Tantui Atas distribution network using ETAP - Marceau Armstrong Fillex Haurissa; Farrel Aqshal Alfarizi Naca (Politeknik Negeri Ambon, 2023)
The process of distributing electricity from power plants to consumers always experiences loss of energy or power losses. Power losses are unavoidable in the distribution network system and if it exceeds the percentage it will harm the distribution network system manager in terms of power or energy distribution. There are two types of shrinkage in the electric power system, namely technical and non-technical shrinkage. Technical depreciation is depreciation that occurs as a result of impedance on generation equipment and distribution equipment in transmission and distribution so that there is lost power. This research is Survey Research, where no changes are made or there is no special treatment of the variables studied. The types of data needed to analyze this calculation are: SLD data, transformer capacity, transformer load, channel length data, conductor type and capacity. The variable used in analyzing the results of this study is the power losses in the Upper Tantui penyulang. Based on the simulation results and also the analysis of the power losses on the Upper Tantui repeater, it can be concluded that the value of power losses during WBP conditions is still in normal conditions, which is below the SPLN standard of 5%, while in the installed load conditions the value of power losses has exceeded the normal limit according to SPLN standards, which is above 5%, where in the installed load conditions the value of power losses has reached 5.48%.